2011
DOI: 10.1532/hsf98.20111048
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Coronary Artery Bypass Grafting in a Low-Volume Center

Abstract: The OPCAB technique is still evolving. Low-volume centers have higher rates of conversion to CPB. Hypotension due to an impaired left ventricular function can be successfully treated by using an IABP. Although blood loss can be managed with BTs, use of a cell saver helps to reduce the number of BTs. We conclude that our technique of total arterial OPCAB using a cell saver can be safely performed in a low-volume center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…There have been reports of use of ventricular assist device to prevent conversions, however, IABP use during OPCAB to prevent conversion has not been reported before. 2 Various studies have suggested that preoperative IABP insertion in high-risk patients may facilitate OPCAB. 3 We perform OPCAB routinely in all isolated coronary artery bypass cases, and use an IABP to treat hemodynamic compromise rather than for preoperative prophylactic use.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of use of ventricular assist device to prevent conversions, however, IABP use during OPCAB to prevent conversion has not been reported before. 2 Various studies have suggested that preoperative IABP insertion in high-risk patients may facilitate OPCAB. 3 We perform OPCAB routinely in all isolated coronary artery bypass cases, and use an IABP to treat hemodynamic compromise rather than for preoperative prophylactic use.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that coronary artery bypass grafting-related bleeding greater than 4 U should be considered an independent risk factor for mortality [Stone 2012]. Some authors suggested that blood cell salvage should be made a conventional measure to improve safety of off-pump coronary artery bypass surgery [Saha 2011]. The application of autologous blood transfusion in off-pump coronary artery bypass grafting has clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…2 We have even successfully performed 9 grafts in a patient using OPCAB. There is no constraint of increasing bypass or clamp time.…”
mentioning
confidence: 94%
“…5 In our series reported earlier, the average number of grafts per patient was >4. 2 We have even successfully performed 9 grafts in a patient using OPCAB. There is no constraint of increasing bypass or clamp time.…”
mentioning
confidence: 94%
See 1 more Smart Citation